Implementation of Creative-Innovative Aspects in the Indonesian Language BSE Evaluation Instrument - Imam Safi'i; Wini Tarmini; Prima Gusti Yanti (Universitas Negeri Makassar, 2022)
This article aims to describe the implementation of the creative-innovative aspects in the evaluation instrument in the Indonesian BSE SMA 2019/2020. The method used is content analysis. The results showed that the four indicators of creative-innovative aspects had been implemented properly. Indicators of developing new ideas were 85 questions or 52.80%, open and responsive as many as 15 questions or 9.32%, expressed creative ideas as many as 40 questions or 24.84%, using concepts in new situations as many as 13 questions or 8, 07%, and creates novelty as much as 8 questions or 4.97%. The results of this study can be used as an assessment of the eligibility of BSE in Indonesian.